Design, development and evaluation of a kenaf pneumatic seeding machine - Bakhtiari, Mohammad Reza (2012)
In this study a 4-row, tractor mounted, kenaf pneumatic seeding machine was designed and developed based on physical, mechanical and aerodynamic properties of kenaf seed (Hibiscus cannabinus L.). The machine is made up of: (a) a chassis which is supported to move across and over fields by at least one drive wheel and one driven wheel (two transportable wheels); (b) four units of planters each consisting of a vacuum seed metering system; furrow opener (furrower); seed opener; seed cover; press wheel; and seed hopper. The vacuum seed metering system (each unit planter has one vacuum seed metering system) includes a seed container, a seed plate having a plurality of circular array openings and tabs, and a cover. The seed container has an adjustable upper cutoff brush and lower cutoff brush to dislodge any extra or double seeds picked up by the seed plate; and a first and second separators; (c) a pulley and vacuum fan to provide negative pressure for vacuum seed metering system; (d) a transmission power system holding a gearbox; chains and sprockets; and pinions and crown wheels to transfer power from drive wheel to the rotating seed plate of the vacuum seed metering system. The pneumatic seeding machine was evaluated both in the laboratory and field using kenaf seeds. For laboratory test, a completely randomized design (CRD) with three replications and for field tests a randomized complete block design (RCBD) with three replications were chosen. The data were analyzed by SAS program version 9.1 and means separation test were done using Duncan’s multiple range test (DMRT). Regression analysis was used to determine the relationship between appropriate pairs of dependent and independent variables. Based on this study, the most suitable opening diameter and opening angle for planting kenaf seed are 3.5 mm and 120o respectively. The results obtained also showed that the most suitable vacuum pressure to pick up and keeping kenaf seed to plant in the soil was more than 3 kPa and the most suitable linear speed belonged to speed range of less than 1.5 km/hr. The average field efficiency of the 4-row pneumatic seeding machine was found to be 74%. The theoretical field capacities for different forward speeds of 2.05, 2.66, 3.63,3.89 and 5.50 km/hr were 2.30, 2.98, 4.07, 4.36 and 6.16 ha/day. Based on these data the economical cost of the developed pneumatic seeding machine was analyzed. The total fixed (ownership) cost was obtained as RM4950/year; while the total variable (operating) cost was found to be RM55.26/hour. Therefore total cost calculated for the machine was RM22189.44/year. Based on this study, if there are 1500 hectares of kenaf plantation area involving 270 growers in Malaysia, for planting kenaf seed twice a year (each time 39 days) and on time, about 35, 24 and 18 of the pneumatic seeding machines are needed for 4-row, 6-row and 8-row planting systems, respectively.